Mode I tensile fracture behavior of adhesively-bonded metal–metal, metal–CFRP, and CFRP–CFRP bi-material combinations analyzed by size effect method. (September 2022) - Qiao, Yao; Merkel, Daniel R.; Nickerson, Ethan K.; Shin, Yongsoon; Seffens, Robert J.; Ortiz, Angel; Simmons, Kevin L.
Abstract: Understanding the adhesive and interfacial fracture is important for developing better adhesive performance in bi-material joints, i.e. adhesive joint between dissimilar materials. However, to characterize the fracturing behavior of various adhesively-bonded materials, it was shown in this work that the Mode I fracture energies estimated from conventional methods ( e.g., work-of-fracture, (modified) compliance calibration method, (modified) beam theory, etc.) can be strongly affected by adherend thickness, adhesive bond length, and adherend material type. Consequently, the proper understanding of fracturing in bi-material joints has been hindered since the estimated fracture energies can exhibit unreasonable difference among various material combinations depending on the method of fracture energy calculation. This has led to confusion in the literature due to the unfair comparison of these non-objective results estimated by leveraging conventional methods on the specimens with different geometries or dissimilar adherend materials. This work introduced the size effect method to adhesively-bonded joints and compared the results with conventional methods of calculating the Mode I fracture energies of metal–metal, metal–CFRP, and CFRP–CFRP material combinations via Double Cantilever Beam (DCB) tests. The results showed that the estimated fracture energies obtained using the size effect method were not dependent on the specimen geometries, whereas conventional methods were strongly dependent on specimen geometry for most material combinations. The size effect method allowed objective comparison particularly on the interfacial fracturing between metal/adhesive and CFRP/adhesive combinations. The difference was further explained by and correlated with the damage morphology on the material surface after failure, which was quantified by three-dimensional profilometer.